Assessment of App Store Description and Privacy Policy to Explore Ethical and Safety Concerns Associated with the Use of Mental Health Apps for Depression. Issue 2 (March 2023) - Singh, Swarndeep; Sharma, Pawan; Ghimire, Pratistha; Shrestha, Roshan; Gnanavel, Sundar
Background: Mental Health apps (MH apps) could help address the huge unmet mental health care need of developing countries. This study aimed to explore potential ethical, data safety, and privacy issues associated with using MH apps for depression. Methods: A cross-sectional assessment of the top 50 MH apps (by Google Play store search result ordering) for depression available in India was conducted in November 2021. Results: Most apps were listed under the category of health and fitness (54%). The median number of total and dangerous permissions requested at the time of download was nine and three, respectively. Privacy policy in English was available for 76%. The average length of the privacy policy was 2171 words, and the mean Flesch-Kincaid reading grade level was 12 (much higher than the recommended cut-off of eight). Important features relevant to safeguarding consumer confidentiality, including names of third parties with which user data could be shared (42%), explicit consent before sharing data with third parties (16%), and assurance regarding the collection of de-identifiable data (11%), were missing from the majority of privacy policies. Conclusion: There is an urgent need to improve the accessibility and usability of privacy policies by app developers, with the active involvement of other stakeholders.